2022
DOI: 10.1088/2632-2153/ac6a51
|View full text |Cite
|
Sign up to set email alerts
|

Multi-task graph neural networks for simultaneous prediction of global and atomic properties in ferromagnetic systems *

Abstract: We introduce a multi-tasking graph convolutional neural network, HydraGNN, to simultaneously predict both global and atomic physical properties and demonstrate with ferromagnetic materials. We train HydraGNN on an open-source ab initio density functional theory (DFT) dataset for iron-platinum (FePt) with a fixed body centered tetragonal (BCT) lattice structure and fixed volume to simultaneously predict the mixing enthalpy (a global feature of the system), the atomic charge transfer, and the atomic magnetic momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…To train a surrogate model for HOMO-LUMO gap prediction, we use the multi-headed HydraGNN package developed earlier by some of our team [18,19]. This surrogate, allowing multi-headed output, is ideally suited for the simultaneous prediction of multiple important molecular characteristics, such as electronic properties and synthesizability scoring.…”
Section: Gcnn Surrogatementioning
confidence: 99%
See 3 more Smart Citations
“…To train a surrogate model for HOMO-LUMO gap prediction, we use the multi-headed HydraGNN package developed earlier by some of our team [18,19]. This surrogate, allowing multi-headed output, is ideally suited for the simultaneous prediction of multiple important molecular characteristics, such as electronic properties and synthesizability scoring.…”
Section: Gcnn Surrogatementioning
confidence: 99%
“…A variety of GCNNs have been developed to better represent the atomic systems, such as crystal GCNN (CGCNN) [43] for crystalline materials, MEGNet for both molecules and crystals [44], as well as ALIGNN [45] that adds the bond angles in the model. More details about GCNNs can be found in [18].…”
Section: Surrogate Models: Graph Convolutional Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work started investigating the effectiveness of GCNN models for prediction of mixing enthalpy, atomic charge transfer, and atomic magnetic moment for solid solution ferromagnetic alloys, characterized by disordered atomic configurations, with non-relaxed crystal structure and fixed volume from open-source DFT data [20,21]. Results showed that the GCNN model can accurately estimate material properties as a function of the configurational entropy [22,23].…”
Section: Introductionmentioning
confidence: 99%